STRATEGI PENINGKATAN MUTU PENDIDIKAN BERBASIS TOTAL QUALITY MANAGEMENT (TQM) DI MADRASAH AL-AZHAR SAMARINDA - Yasinta Quraini Nurdiniyya; Bahrani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the strategy for improving educational quality based on Total Quality Management (TQM) at MTs Al-Azhar Samarinda. A descriptive qualitative approach was used to examine the implementation of the three core principles of TQM: customer focus, continuous improvement, and employee involvement. The findings indicate that MTs Al-Azhar has adopted these principles by delivering educational services that emphasize student and parent satisfaction, conducting regular program evaluations, and involving teachers and staff in quality management. Despite challenges such as limited resources and resistance to change, the strategy has proven effective in fostering a quality culture and gradually improving educational standards.